2022
DOI: 10.1080/10429247.2022.2147381
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence and the UK Construction Industry – Empirical Study

Abstract: There is a lack of research on the use of Artificial Intelligence (AI) within the construction sector in the UK. Therefore, this research seeks to explore AI uses and its benefits on the UK construction industry. Given the new and unexplored nature of the research problem, a qualitative case study research methodology was adopted. Construction projects, which have adopted some of the AI forms all around the UK, are investigated extracting the use of the technology and how processes within the construction indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Quantitative information from the reviews uncovered that 75% of associations have coordinated artificial intelligence fueled apparatuses and advancements into their project management processes in some limit (Smith et al, 2022). Besides, research of study reactions demonstrated that associations revealed a normal increment of roughly 25% in project achievement rates following the reception of artificial intelligence in project management rehearse (Jones, 2021). Qualitative information from interviews gave important experiences into the particular jobs of artificial intelligence in project management, remembering its effect for dynamic cycles, asset allotment, and risk management .…”
Section: Percentagesmentioning
confidence: 99%
“…Quantitative information from the reviews uncovered that 75% of associations have coordinated artificial intelligence fueled apparatuses and advancements into their project management processes in some limit (Smith et al, 2022). Besides, research of study reactions demonstrated that associations revealed a normal increment of roughly 25% in project achievement rates following the reception of artificial intelligence in project management rehearse (Jones, 2021). Qualitative information from interviews gave important experiences into the particular jobs of artificial intelligence in project management, remembering its effect for dynamic cycles, asset allotment, and risk management .…”
Section: Percentagesmentioning
confidence: 99%
“…Similarly, existing AI implementation and its benefits were assessed in the UK's construction industry. It was recommended that organisations consider AI's implementation in the future to become competitive [98].…”
Section: Coding and Programmingmentioning
confidence: 99%
“…In some other fields, scholars often adopt qualitative research methods. Jallow et al [8] adopted a qualitative case study research methodology to explore the uses of AI and its benefits for the UK construction industry. In the retail field, Pillai et al [9] surveyed 1250 consumers to investigate their shopping intentions at AI-powered automated retail stores.…”
Section: Literature Reviewmentioning
confidence: 99%